2018
DOI: 10.1111/medu.13581
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking medical oaths using the Physician Charter and ethical virtues

Abstract: Medical oaths in North America appear to be highly variable in content. Greater attention to resources like the Physician Charter can help improve the ethical content and consistency of oaths across different institutions, and throughout their education medical students should be encouraged to discuss and reflect on the principles and virtues they will profess when they graduate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Being aware of those values has become even more important now as medical educators start to recognise the importance of professional identity formation as a dominant goal of medical education 1. We therefore commend Greiner and Kaldjian for their paper reporting a content analysis of medical oaths taken in the USA and Canada,2 published in this issue of Medical Education . However, we do ask ourselves why the authors2 restricted their study to North America, and how we should interpret the observed plurality of medical oaths.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Being aware of those values has become even more important now as medical educators start to recognise the importance of professional identity formation as a dominant goal of medical education 1. We therefore commend Greiner and Kaldjian for their paper reporting a content analysis of medical oaths taken in the USA and Canada,2 published in this issue of Medical Education . However, we do ask ourselves why the authors2 restricted their study to North America, and how we should interpret the observed plurality of medical oaths.…”
mentioning
confidence: 99%
“…We therefore commend Greiner and Kaldjian for their paper reporting a content analysis of medical oaths taken in the USA and Canada,2 published in this issue of Medical Education . However, we do ask ourselves why the authors2 restricted their study to North America, and how we should interpret the observed plurality of medical oaths. In this commentary, we want to address three issues:…”
mentioning
confidence: 99%
See 3 more Smart Citations